Influence of emotional intelligence on students’ academic achievements - Ngu, Leh Seng; Hanafi, Zahyah; Taslikhan, Muhajir; Raman, Arumugam (2016)
Emotional aspects are very important in influencing the excellence of a student.Many past studies have proven that emotional intelligence affect academic achievement. Therefore, this study is aimed to identify students’ emotional intelligence level and to what extent emotional intelligence influences students’ academic achievement.A total of 406 people form 5 students from nine schools in Limbang District, Sarawak were involved in this study. Malaysia Intelligence Emotional Inventory – Teens (IKEM-R) was used to assess the level of students’ emotional intelligence.A total of 49 items from this instrument was used to measure emotional intelligence of the respondents.Exploratory factor analysis and KMO value for pilot study is.607. The result of the study show that all the emotional intelligence dimensions are at high level.Further, the results revealed that there is no significant influence of all the dimensions on academic achievement.Five research hypotheses were supported.All the emotional intelligence dimensions namely emotional awareness, emotional regulation, self-motivation, empathy and social skills do not affect students' academic achievement.